Cutting thin glass by femtosecond laser ablation. (June 2018) - Shin, Hyesung; Kim, Dongsik
Highlights: Thin glass cutting process using femtosecond laser ablation is analyzed. Processing parameters are optimized to maximize the cutting speed and edge strength. Cutting speed is proportional to fluence unless the overlap ratio exceeds a critical value. High edge strength in laser-cut thin glass requires low fluence and high overlap ratio. Polarization should be vertical to cutting path for better cutting performance. Abstract: The femtosecond laser ablation process for cutting thin aluminoborosilicate glass sheets of thickness 100 μm was investigated with emphasis on effective cutting speed ( V eff ) and mechanical strength of diced samples. The process parameters including the laser fluence ( F ), overlap ratio ( r ) of the laser beam and polarization direction were varied at a fixed pulse repetition rate f  = 1 kHz to find the optimal process condition that maximizes V eff and edge strength. A three-point bending test was performed to evaluate the front-side and back-side bending (edge) strength of the laser-cut samples. V eff was proportional to F unless r exceeded a critical value, at which excessive energy began to be delivered at the same spot. The front-side edge strength was bigger than the back-side strength because of the back-side damages such as chipping. Good edge strength, as high as ∼280 MPa (front-side) and ∼230 MPa (back-side), was obtained at F  = 19 J/m 2, r  = 0.99, with laser polarization vertical to the cutting path.